Criminal Law Enforcement Against Illegal Cosmetic Products: A Normative Juridical Study - Recha Redian; Bangun Patrianto (jfpublisher, 2026)
The widespread circulation of illegal cosmetic products poses serious threats to consumer health and safety, particularly those containing hazardous substances such as mercury and hydroquinone distributed without valid regulatory authorization. This study examines criminal law enforcement against perpetrators of illegal cosmetic distribution and the legal protection afforded to consumers within the jurisdiction of the East Java Regional Police (Polda Jawa Timur). Employing a normative juridical method with a statute approach, this study analyzes applicable provisions under Law No. 36 of 2009 on Health and Law No. 8 of 1999 on Consumer Protection, using the counterfeiting of New KLT cosmetic products as its primary case reference. The findings reveal that while the existing statutory framework provides a sufficient normative basis for criminal prosecution, enforcement effectiveness is constrained by inadequate inter-agency coordination between the Regional Police and BPOM, the proliferation of unmonitored online distribution channels, and the absence of accessible victim compensation mechanisms. This study extends prior research by demonstrating that administrative supervision and criminal law enforcement function as complementary rather than substitutable instruments, and that consistent police-led prosecution is indispensable to closing the deterrence gap that regulatory reform alone cannot address. Stricter sanction implementation and strengthened institutional coordination are recommended to optimize consumer protection outcomes.